Cover Picture: The Influence of Nanoscale Heterostructures on the Thermoelectric Properties of Bi‐substituted Tl5Te3 (Z. Anorg. Allg. Chem. 6/2017). Issue 6 (16th March 2017) - Heinke, Frank; Eisenburger, Lucien; Schlegel, Robert; Schwarzmüller, Stefan; Oeckler, Oliver
Abstract : The background of the cover image displays a backscattered electron SEM image (with inverted colors, width ca. 3 µm) of a nanostructured sample with the nominal composition (Tl4.5 Bi0.5 Te3 )0.6 (TlInTe2 )0.4 . The light blue areas indicate correspond to TlInTe2 whereas the dark blue ones originate from Tl4.5 Bi0.5 Te3 . In the crystal structure of Tl4.5 Bi0.5 Te3 in the foreground, arrows indicate the distortion compared to Tl5 Te3 . The structure was elucidated by resonant powder X‐ray diffraction. In the graph at the bottom, the overall thermal conductivities of pure Tl4.5 Bi0.5 Te3 and the nanostructured sample (Tl4.5 Bi0.5 Te3 )0.6 (TlInTe2 )0.4 are compared, indicating the better performance of the composite at elevated temperatures. More details can be found in the article by Heinke and Oeckler et al. on page447 ff .